Emotion Detection Deficits and Decreased Empathy in Patients with Alzheimer’s Disease and Parkinson’s Disease Affect Caregiver Mood and Burden - Martinez, Maria; Multani, Namita; Anor, Cassandra J.; Misquitta, Karen; Tang-Wai, David F.; Keren, Ron; Fox, Susan; Lang, Anthony E.; Marras, Connie; Tartaglia, Maria C. (Frontiers in Aging Neuroscience, 2018)
Background: Changes in social cognition occur in patients with Alzheimer’s disease and Parkinson’s disease and can be caused by several factors, including emotion recognition deficits and neuropsychiatric symptoms. The aims of this study were to investigate: 1) group differences on emotion detection between patients diagnosed with Alzheimer’s disease or Parkinson’s disease and their respective caregivers 2) the association of emotion detection with empathetic ability and neuropsychiatric symptoms in individuals with Alzheimer’s disease or Parkinson’s disease; 3) caregivers’ depression and perceived burden in relation to patients’ ability to detect emotions, empathize with others, presence of neuropsychiatric symptoms and (4) caregiver’s awareness of emotion detection deficits in patients with Alzheimer’s disease or Parkinson . Methods: In this study, patients with probable Alzheimer’s disease (N = 25) or Parkinson’s disease (N = 17), and their caregivers (N = 42), performed an emotion detection task (The Awareness of Social Inference Test – Emotion Evaluation Test). Patients underwent cognitive assessment, using the Behavioral Neurology Assessment. In addition, caregivers completed questionnaires to measure empathy (Interpersonal Reactivity Index) and neuropsychiatric symptoms (Neuropsychiatric Inventory) in patients and self-reported on depression (Geriatric Depression Scale) and burden (Zarit Burden Interview). Caregivers were also interviewed to measure dementia severity (Clinical Dementia Rating Scale) in patients. Results: The results suggest that individuals with Alzheimer’s disease and Parkinson’s disease are significantly worse at recognizing emotions than their caregivers. Moreover, caregivers failed to recognize patients’ emotion recognition deficits and this was associated with increased caregiver burden and depression. Patients’ emotion recognition deficits, decreased empathy and neuropsychiatric symptoms were also related to caregiver burden and depression. Conclusions: Changes in emotion detection and empathy in individuals with Alzheimer’s disease and Parkinson’s disease has implications for caregiver burden and depression and may be amenable to interventions with both patients and caregivers.